Learning word class in a second language through vocabulary learning activities: definition-choosing, gap-filling, and sentence-writing. (2nd January 2019) - San-Mateo-Valdehíta, Alicia; Chacón-García, Carmen
ABSTRACT: This article presents the results of a research project investigating how a student's ability to successfully learn vocabulary of four word classes (nouns, adjectives, verbs and adverbs) is affected by the activity through which it is practised. Two-hundred and ninety-two B1 SL students of Spanish were presented with one of three different activities requiring different involvement loads: (1) choosing the appropriate definition; (2) filling in gaps in sentences; and (3) writing sentences that include target words. The analysis shows that participants recalled and recognised more nouns and fewer adverbs—the only non-inflected word class. Additionally, sentence-writing is the activity through which learning new words is the easiest; and the least effective is the definition-choosing activity.